Johnny Quick - Lyga, Barry (Lyga, Barry. Flash, 2018)
Still shaken by the magic and disappearance of Hocus Pocus, Flash travels to Earth-2--the exact opposite of Earth-1--to discover the truth. But the Flash is the villain in this new place, and though Johnny Quick looks and acts like the Flash, Barry Allen knows that to get answers--and get home--he must beat the new speedster at his own game.